THE WORD “EDUCATION” IN SOCIAL MEDIA - TÜRKER, İlker; TAN, Serhat Orkun (The Eurasia Proceedings of Educational and Social Sciences, 2016)
The word education, which can be expressed as a systematic way of giving the knowledge and skills to the individuals, is mentioned frequently in social media. The fastest-growing network twitter is also the optimal platform to get information from the usage of the “education” word by social communities. From this point of view, utilizing from twitter, this study aimed to investigate how the word “education” is used in social media. The usage frequency of the word “education”, the most frequently used terms together with the word “education” and also the location information of education tweets were acquired to evaluate the comments of the individuals on the word. The followings and followers numbers of the people who make education sharing are also stated to see the popularity of these people in social media.